Far Distance Blurry Vision Following Rhinoplasty - Shushtarian, Seyed Mohammad Masoud; Pour Mazar, Reza (Journal of Ophthalmic and Optometric Sciences, 2021)
Rhinoplasty surgery changes the shape of the nose. The motivation for rhinoplasty may be to change the appearance of the nose, improve breathing, or both. A 25-year-old patient was referred to the Basir clinic for a visual evoked potential (VEP) examination. The patient complained from far distance blurry vision after rhinoplasty. Her magnetic resonance imaging (HRI) and VEP examination were normal. The present work explains her case.